Código Civil y Reforma en el Perú: Un repaso histórico. Entrevista a Jorge Avendaño Valdez - Roca Lizarzaburu, Luis Fernando (2014)
The reform of the text and the enactment of a new Civil Code both require a long and careful process; the work of a Reformer Commission should focus on   identifying areas for improvement in the text and propose solutions to the problems that may have occurred in theimplementation of the revised text.In this interview, Jorge Avendaño talks about his experience working in the Reformer Commissions of 1936 and 1984’s Civil Codes, the second of which he personally presided. He also refers to the proposals he made to the Book of Rights in Rem and the feasibility of its implementation.